CLASSROOM ACTION RESEARCH IN THE PERSPECTIVE OF TEACHER PROFESSIONALISM: A THEORETICAL STUDY AND ITS IMPLICATIONS - Ervina Ervina; Dwi Rahmah Fitri; Fitri Barokah; Zalia Sari (PT. Jurnal Center Indonesia Publisher, 2025)
Classroom Action Research (PTK) is a scientific approach that not only functions as a solution to learning problems in the classroom, but also as a strategic means in developing teacher professionalism. Through systematic reflection and continuous improvement, PTK encourages teachers to improve their pedagogical, professional, social, and personality competencies. Theoretically, PTK strengthens the foundations of constructivism and reflective learning practices, allowing teachers to dynamically connect theory and classroom reality. From a practical perspective, PTK has a direct impact on improving the quality of learning, student involvement, and changing teachers' professional attitudes. Although its implementation is faced with various challenges, both technical and psychological, solutions can be found through ongoing training, mentoring, and institutional support. Thus, PTK plays an important role in building an innovative work culture and improving the quality of education holistically.